Lesión vascular en pacientes con síndrome coronario agudo en el Hospital General de las Fuerzas Armadas Quito N° 1 - Granda Vélez, Ximena del Carmen (2015)
Acute Coronary Syndrome (ACS) is the loss of balance between the supply and demand of oxygen, comprising: unstable angina (UA) , acute myocardial infarction ( AMI ) with ST elevation and non-ST elevation, treatment is by thrombolytic therapy or angioplasty. From this perspective, the present study aims to determine the degree of vascular injury in patients with acute coronary syndrome which constitutes a major public health problem worldwide. In recent years there have been many advances in the epidemiology, pathophysiology and treatment which have impacted on the management guidelines and prognosis of these patients. Therefore, the study is retrospective, descriptive and transversal in which we reviewed medical records of 222 patients diagnosed with ACS who were hospitalized in the cardiology department of HE - 1, we evaluated its presentation according to gender, risk factors and extent of coronary vessel injury by angiography. Through the research process undertaken, it was shown that the presentation of SCA most often is in the masculine gender with 69 %, the risk factors in man and woman were hypertension 28 % and 32% respectively, diabetes mellitus 26 % in women and smoking by 20 % in men . Cardiac catheterization was performed in 100% of cases , 2 blood vessels were affected by more than 40 % and was frequently injured anterior descending artery with 41% in men and 56 % in women , stent was placed over 80 % of cases . Keywords: Acute Coronary Syndrome, Vascular Lesion, Angiography